Vector algebra theory in analysis of properties of antibacterial medications - Boyko, N; Zaytsev, A; Osolodchenko, T (Annals of Mechnikov's Institute, 2020)
The possibility to use vector algebra theory for quantitative description of antibacterial medications and comparison of their properties has been shown. Mathematic formulas for description of medications’ antibacterial action basing on data of simple to use well method have been presented. This method allows evaluation of medications’ antibacterial activity and opportunity to choose the most active ones, as well as compare them with each other. It is noted that medications of natural origin are inferior to those of synthetic origin as for their antibacterial activity and new galenic medications possess the most antimicrobial properties. The prospects of this method for pharmacoeconomic analysis of medications conducted in order to chose optimal cost/quality ratio has been demonstrated.